Religious Nationalism of Kèaè Pesantren: K.H. Zainal Arifin Together with Oreng Kenek Builds Nationality and Curbs Colonialism in Sumenep - Iskamar; Abd A'la; Damanhuri (Pascasarjana Universitas KH. Abdul Chalim, 2025)
The spread of Islam brought by K.H. Zainal Arifin, one of Syaikhona Kholil Bangkalan's students who born in Sumenep, has a unique scheme because it intersects with Islamic preaching on the one hand, and fighting colonialism on the other. This article aims to describe the religious nationalism of K.H. Zainal Arifin was recorded in his movement defending the interests of